ENVIRONMENTAL ASSESSMENT OF COBALT AT WUDIL, KANO STATE NIGERIA - Alkhatib, Ahed J; Muhammad, Murtala; Habib, Ishaq Y; Idris, Idris M; Adamu, Auwal; Bala, Sani S (European Scientific Journal, ESJ, 2014)
Introduction: Environmental safety is a large concern at global level. There are numerous bad behaviors that impact environment. Environmental assessment for contamination of heavy metals is an important step to put right policies for environmental protection. Objectives: The present study was conducted to assess the environmental impacts of Cobalt at Wudil, Kano State Nigeria. Cobalt was screened in water, soil, and some vegetables including lettuce, spinach and onion. Methodology: Study methodology involved taking random samples representing Wudil environment including random samples from soil, water, and vegetables. All samples were prepared and processed to be ready for assaying for cobalt using Atomic absorption spectrometry. Results: Study findings showed that he mean concentration of cobalt in soil samples at Wudil was 76.22±8.99 μg/g, and in water, it was 0.122±0.08 mg/l. In lettuce, the mean concentration of cobalt was 174.797±14.08 mg/kg, in spinach, 101.63±7.04 mg/kg, and in onion 154.47±18.63mg/kg. Conclusions: our data demonstrated that cobalt is an environmental pollutant at Wudil, Kano State Nigeria.